تقييم دور حاضنات الأعمال في إنشاء ودعم المشاريع المقاولاتية في الج ا زئر د ا رسة حالة مشتلة المؤسسات- محضنة بات - سعودي عبد الصمد (Finance and Business Economies Review, 2017)
to work Entrepreneurial great importance in the economies of developed and developing countries alike, through active participation in the operating contribution, as well as its ability to adapt to changes and different economic, and despite the importance, but it faces many of the problems that hindered in Algeria, so shall Algeria find appropriate ways to support mechanisms, most notably the so-called incubators business that are important in the development of contracting and small and medium enterprises mechanisms by helping to provide the initial impetus and ensure sustainability through what they provide support, especially in the early stages and support services. In order to highlight the more we have a field study Incubator institutions Batna where we stood on this pioneering experiment that still need more support and development, has been able within a short accompaniment of many institutions and successful contracting.